THE ESSENTIALS OF A GENERAL THEORY OF DEPRECIATION. - Lowe, Howard D. (The Accounting Review, 1963)
Abstract The shift in emphasis by the accounting profession from the statement of financial condition to the income statement, and more recently to a management approach has been associated with a rise in the relative importance of investor and manager groups and an increasing realization of the usefulness of quantitative data in making executive decisions. Accounting for the consumption of long-lived assets has been influenced by these changes in emphasis and this has led to considerable disagreement and confusion regarding certain problems related to depreciation. Many schemes have been advanced for transferring the expired cost of depreciable assets to operations. At one extreme a few businessmen have been influenced by the payout technique for budgeting capital items and advocate the immediate transferal of the entire cost upon incurrence to expense. The article laid the foundation for the development of a theory of depreciation with objectives reflecting the current emphasis in accounting. The theory is based upon recommended principles of economics and accounting and it satisfies the decision-making requirements of management.